NRDE-2, the human homolog of fission yeast Nrl1, prevents DNA damage accumulation in human cells. Issue 7 (3rd July 2018) - Richard, Patricia; Ogami, Koichi; Chen, Yaqiong; Feng, Shuang; Moresco, James J.; Yates, John R.; Manley, James L.
ABSTRACT: The RNA helicase Mtr4 is a versatile protein that is a crucial component of several distinct RNA surveillance complexes. Here we describe a novel complex that contains Mtr4, but has a role distinct from any of those previously described. We found that Mtr4 association with the human homolog of fission yeast Nrl1, NRDE-2, defines a novel function for Mtr4 in the DNA damage response pathway. We provide biochemical evidence that Mtr4 and NRDE-2 are part of the same complex and show that both proteins play a role in the DNA damage response by maintaining low DNA double-strand break levels. Importantly, the DNA damage response function of the Mtr4/NRDE-2 complex does not depend on the formation of R loops. We show however that NRDE-2 and Mtr4 can affect R-loop signals at a subset of distinct genes, possibly regulating their expression. Our work not only expands the wide range of Mtr4 functions, but also elucidates an important role of the less characterized human NRDE-2 protein.